Associations between psychopathic traits and brain activity during instructed false responding - Glenn, Andrea L. (Psychiatry Res, 2017)
Lying is one of the characteristic features of psychopathy, and has been recognized in clinical and diagnostic descriptions of the disorder, yet individuals with psychopathic traits have been found to have reduced neural activity in many of the brain regions that are important for lying. In this study, we examine brain activity in sixteen individuals with varying degrees of psychopathic traits during a task in which they are instructed to falsify information or tell the truth about autobiographical and non-autobiographical facts, some of which was related to criminal behavior. We found that psychopathic traits were primarily associated with increased activity in the anterior cingulate, various regions of the prefrontal cortex, insula, angular gyrus, and the inferior parietal lobe when participants falsified information of any type. Associations tended to be stronger when participants falsified information about criminal behaviors. Although this study was conducted in a small sample of individuals and the task used has limited ecological validity, these findings support a growing body of literature suggesting that in some contexts, individuals with higher levels of psychopathic traits may demonstrate heightened levels of brain activity.